Effect of Fluoride Toothpaste Containing Nano-Sized Sodium Hexametaphosphate on Enamel Remineralization: An in situ Study - Danelon, Marcelle [UNESP]; Garcia, Luhana G. [UNESP]; Pessan, Juliano P. [UNESP]; Passarinho, Amanda [UNESP]; Camargo, Emerson R.; Delbem, Alberto C.B. [UNESP] (Karger Publishers, 2019)
Objective: To evaluate the remineralizing potential of a conventional toothpaste (1,100 ppm F) supplemented with nano-sized sodium hexametaphosphate (HMPnano) in artificial caries lesions in situ. Design: This double-blinded crossed study was performed in 4 phases of 3 days each. Twelve subjects used palatal appliances containing 4 bovine enamel blocks with artificial caries lesions. Volunteers were randomly assigned into the following treatment groups: no F/HMP/HMPnano (Placebo); 1,100 ppm F (1100F); 1100F plus 0.5% micrometric HMP (1100F/HMP) and 1100F plus 0.5% nano-sized HMP (1100F/HMPnano). Volunteers were instructed to brush their natural teeth with the palatal appliances in the mouth for 1 min (3 times/day), so that blocks were treated with natural slurries of toothpastes. After each phase, surface hardness post-remineralization (SH2), integrated recovery of subsurface hardness (ΔIHR), integrated mineral recovery (ΔIMR) and enamel F concentration were determined. Data were submitted to analysis of variance and Student-Newman-Keuls' test (p < 0.001). Results: Enamel surface became 42% harder when treated with 1100F/HMPnano in comparison with 1100F (p < 0.001). Treatment with 1100F/HMP and 1100F/HMPnano promoted an increase of ∼23 and ∼87%, respectively, in ΔIHR when compared to 1100F (p < 0.001). In addition, ΔIMR for the 1100F/HMPnano was ∼75 and ∼33% higher when compared to 1100F and 1100F/HMP respectively (p < 0.001). Enamel F uptake was similar among all groups except for the placebo (p < 0.001). Conclusion: The addition of 0.5% HMPnano to a conventional fluoride toothpaste was able to promote an additional remineralizing effect of artificial caries lesions.
Keywords: Dental enamel; Nano-sized; Phosphate; Remineralization; Toothpaste